Successful antibiotic treatment of liver abscess in an eight-year-old boy after perforated appendix - Marko Bašković; Antun Kljenak; Ante Čizmić; Dora Škrljak Šoša; Katarina Vulin; Ivana Đaković (Hygeia Press di Corridori Marinella, 2021)
We present the case of an eight-year-old boy who was referred to our Clinic with acute abdomen. After ultrasound, which showed a perforated appendix, an urgent appendectomy was initiated. When the peritoneum was opened, the abdomen was full of pus. The appendix was positioned retrocecal and subhepatic, extensively coupled with the ascendant colon. Partial omentectomy and appendectomy were performed. On the tenth postoperative day, a contrast-enhanced ultrasound (CEUS) was performed. A subcapsular lesion of the right liver lobe of 30 mm diameter was observed. It was a liver abscess. Three weeks after intravenous therapy (clindamycin/gentamicin, piperacillin/tazobactam), the abscess has completely regressed.